Generation Z and ethicality of advancement in the workplace: a study of Slovenia and Lithuania - Nedelko, Zlatko; Peleckienė, Valentina; Peleckis, Kęstutis; Peleckis, Kestutis K.; Lapinskienė, Giedrė; Potocan, Vojko (Journal of Business Economics and Management, 2022)
The main purpose of this study was to examine the ethicality of future employees’ attitudes toward advancement in the workplace in Slovenia and Lithuania. This study focuses on students representing young adults from Generation Z as future employees in organizations. Using a survey of work-related issues, we collected 212 answers from Slovenian and 159 from Lithuanian’ students from business faculties. We used t-tests and regression analyses to obtain results. We found that the future employees in Slovenia see organizationally beneficial behavior and self-indulgent behavior significantly more acceptable for their advancement, than their Lithuanian peers. No differences exist in the perception of destructive behavior among participants from both countries. Substantial differences in the importance of personal values ​​among Generation Z members in both societies, provide a strong support for the divergence nature of Generation Z across cultures. The impact of personal values on the ethicality of different behavior for advancement in the workplace among future employees in both societies is substantial, but biased and follows different patterns. In Slovenia, the dominant role has power, followed by hedonism, benevolence, security, conformity, tradition, and universalism, while in Lithuania, the dominant role belongs to self-direction, followed by tradition, universalism, security, achievement, and power. This study will help us to understand Generation Z values and their perceptions regarding ethicality of advancement in the workplace and enable organizations to manage the behavior of future employees.